Q. 3 F

Simplify the following expressions:

(a4 – b4) ÷ (a – b)

Answer :

Factorize the numerator,


a4 – b4 = (a2)2 – (b2)2


= (a2 + b2)(a2 – b2) [ a2 – b2 = (a + b)(a – b)]


= (a2 + b2)(a + b)(a – b) [ a2 – b2 = (a + b)(a – b)]


Now,




= (a2 + b2)(a + b)


Rate this question :

How useful is this solution?
We strive to provide quality solutions. Please rate us to serve you better.
Related Videos
Champ Quiz | Linear Equation in One Variable44 mins
Discussion on Algebric Identities48 mins
Try our Mini CourseMaster Important Topics in 7 DaysLearn from IITians, NITians, Doctors & Academic Experts
Dedicated counsellor for each student
24X7 Doubt Resolution
Daily Report Card
Detailed Performance Evaluation
view all courses